The frequencies and disparities of adverse childhood experiences in the U.S. - Zachary Giano; Denna L. Wheeler; Randolph D. Hubach (BMC, 2020)
Abstract Background Adversity experienced during childhood manifests deleteriously across the lifespan. This study provides updated frequency estimates of ACEs using the most comprehensive and geographically diverse sample to date. Methods ACEs data were collected via BRFSS (Behavioral Risk Factor Surveillance System). Data from a total of 211,376 adults across 34 states were analyzed. The ACEs survey is comprised of 8 domains: physical/emotional/sexual abuse, household mental illness, household substance use, household domestic violence, incarcerated household member, and parental separation/divorce. Frequencies were calculated for each domain and summed to derive mean ACE scores. Findings were weighted and stratified by demographic variables. Group differences were assessed by post-estimation F-tests. Results Most individuals experienced at least one ACE (57.8%) with 21.5% experiencing 3+ ACEs. F-tests showed females had significantly higher ACEs than males (1.64 to 1.46). Multiracial individuals had a significantly higher ACEs (2.39) than all other races/ethnicities, while White individuals had significantly lower mean ACE scores (1.53) than Black (1.66) or Hispanic (1.63) individuals. The 25-to-34 age group had a significantly higher mean ACE score than any other group (1.98). Generally, those with higher income/educational attainment had lower mean ACE scores than those with lower income/educational attainment. Sexual minority individuals had higher ACEs than straight individuals, with significantly higher ACEs in bisexual individuals (3.01). Conclusion Findings highlight that childhood adversity is common across sociodemographic, yet higher in certain categories. Identifying at-risk populations for higher ACEs is essential to improving the health outcomes and attainment across the lifespan.